Optimasi Pola Tanam Usahatani Sayuran Selada dan Sawi di Daerah Produksi Padi (Studi Kasus di Desa Lam Seunong, Kecamatan Kota Baro, Kabupaten Aceh Besar) - Khalik R; Safrida Safrida; Ahmad Humam Hamid (Jurnal Agrisep, 2013)
ABSTRACT. Farming is a plot of land or a part of the earth's surface where the farmers and their families to grow crops or raise livestock. A farmer faced with the enigma to determining the competition of activity in optimizing farming activities. The research was done in Lam Seunong village, Kecamatan Kota Baro, Aceh Besar, the object of research is the farmers who worked in rice, mustard and lettuce land farm. The purpose of this research was to know optimal cropping pattern for mustard and lettuce farming in rice production areas in an effort to increase the optimize income of farmers. The research using purposive sampling techniques with particular sampling, analytical methods using linear programming optimization. The results showed the optimal cropping pattern in the local rice production area is rice and mustard greens in the first season and lettuce in the second season that will obtain maximum revenue of Rp. 76,568,940.00 per period of the rice planting season. With an area of arable land each season is 0.3 hectare for rice in the first season, 0.26 hectare for mustard in the first season, and 0.26 hectare for lettuce second season.